Beneficial Effects of Traditional Chinese Medicine on the Treatment of Osteoporosis on Ovariectomised Rat Models - Rufus, Pamela; Mohamed, Norazlina; Nazrun Shuid, Ahmad (Current Drug Targets, 2013)
Osteoporosis is a metabolic bone disorder that affects both men and women worldwide. It causes low bone mass and therefore increases bone susceptibility to fracture when bone undergoes a minor trauma. Lack of estrogen is the principal cause of osteoporosis. Estrogen, calcium, calcitonin, vitamin D and several antioxidants help in the prevention of osteoporosis. In order to effectively treat osteoporosis, there has been an extended research on the biological activities of traditional medicines since synthetic medicines possess several side effects that reduce their efficacy. Therefore, there is a need to develop new treatment alternatives for osteoporosis. This review centres on the scientific researches carried out on the evaluation of Chinese traditional medicines in the treatment of osteoporosis. Various plants like Achyranthes bidentata, Davallia formosana, polygonatum sibiricum, Cibotium barometz, Er-Zhi-Wan, Curculigo orchioides and a combined treatment of Hachimi-jio-gan (Ba-Wei-Di-Huang-Wan) with alendronate proved active in preventing post-menopausal osteoporosis.
Keywords: traditional Chinese medicine